Challenges of Male Students of Home Economics in Tertiary Institution in Anambra State - E. N., Emeka-Okafor; N. G., Onyeke (Journal of Home Economics Research, 2024)
This study investigated the challenges faced by male students of Home Economics in tertiary institutions in Anambra State. Five research questions were answered. It adopted a survey research. The population for the study was 260 students offering Home Economics as a course of study in tertiary institutions. Questionnaire was used for data collection. Data were analysed using mean. Findings include, among others, 13 family-related challenges, eight society-related challenges, 22 self and peers-related challenges. It was recommended that adequate public awareness programmes should be mounted on the prospects and career opportunities in Home Economics; parents should not discriminate among their children on choice of courses; and government should pay adequate attention to Home Economics education by providing funds, equipment and training for the teachers.